2009 4th International Symposium on Wireless Pervasive Computing 2009
DOI: 10.1109/iswpc.2009.4800586
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pilot-Aided Channel Estimation in Zero Padded MC-CDMA Systems

Abstract: This paper considers two simple procedures to improve the channel frequency response estimate for uplink Zero Padded MC-CDMA systems. The first approach uses a precomputed matrix that projects the original discrete frequency response onto the subspace where the true frequency response lies. The second uses a constrained MMSE optimization that forces the estimate to belong to this subspace. Analytical expressions for the mean square error and its upper and lower bounds are presented for the conventional and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Looking from a different perspective [29], [30], [31], [32], it can be shown that this procedure is equivalent to projecting the original channel frequency response estimate in the subspace generated by the first L columns of the DFT matrix F M,M . Note that by virtue of (3) the true frequency response of the channel has to lie in this subspace.…”
Section: A Improved Channel Estimatormentioning
confidence: 99%
See 3 more Smart Citations
“…Looking from a different perspective [29], [30], [31], [32], it can be shown that this procedure is equivalent to projecting the original channel frequency response estimate in the subspace generated by the first L columns of the DFT matrix F M,M . Note that by virtue of (3) the true frequency response of the channel has to lie in this subspace.…”
Section: A Improved Channel Estimatormentioning
confidence: 99%
“…where λ min and λ max are the minimum and maximum eigenvalues of D w F as defined in (30), respectively. The comparison of (27) and (31) motivates the defintion of the MAI reduction factor η as:…”
Section: B Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Estimadores de canal já são bem conhecidos na literatura para sistemas CDMA [5] e, também, já apresentados para modulações OFDM [6]. Para o sistema MC-CDMA, foco deste trabalho, a novidade consiste em, partindo de [6], explorar um novo enfoqueàquela idéia por meio de uma matriz de projeção que projeta a estimativa de canal no subespaço onde a verdadeira resposta de frequência do equivalente discreto do canal está contida [7], [8], [9]. São apresentadas análises estatísticas e expressões para limitantes do erro médio quadrático dos estimadores, que independem das características do canal.…”
Section: Introductionunclassified